Terminological consistency as the linguodidactic aspect of the research of the Language for Special Purposes - Anafinova М.Л.; Yessengeldinova А.Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The development of technologies and innovations in the modern world, as well as the communicative professional sphere, has led to greater attention to teaching at the pre-professional and professional levels of a special language. The linguo-didactic approach to the LSP as a system of concepts of a specific field of knowledge and their classification are determined by the processes of interaction, interpenetration and mutual influence of multilingual vocabulary from various professional fields. The conducted analysis allows us to consider the LSP as a complex system that is able to provide the main language functions: systematization of knowledge in a certain field of professional domain and the designation of concepts of the relevant field of knowledge, and their coherence for use in a practical perspective. The article presents the theoretical and practical justification of the terminological consistency of the LSP and shows by examples the possibilities and achievements of integrative research through the analysis of trilingual and intersubject terms in the context of the modern multilingual dimension.